Sebastian Smith: capstone - Smith, Sebastian, artist (Colorado State University. Libraries, 2016)
The artist's statement: Through my work, I aim to bring to the forefront of our experience the universal thoughts, emotions, and experiences that connect us as humans. I am fascinated by the human figure and juxtaposing it with formal abstract forms to create this unifying experience between viewers. An angry face, a grasping hand, these are actions which every viewer can understand and relate to. Similarly, formal, abstract forms such as sharp points or soft edges play on our visual vocabulary in an almost universal way. The abstractions juxtaposed with the figure create a dialogue which enriches the viewers understanding and connection to the piece that the use of one of these elements could not do. Using these elements in three dimensional space allows for the viewer to connect with it in a natural manner as our experience of life is in three dimensions. It also allows me to utilize various materials that add to the content of the piece. For example, steel is strong and structural, stone has a rich historical background in the decorative arts, and clay is of the earth as we are. These often unconscious associations help to direct the viewer to the concepts I wish to convey.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: sculpture